Sistem Informasi Pengajuan Judul Skripsi Mahasiswa Program Studi Teknik Informatika (Studi Kasus Fakultas Teknik Universitas Ibnu Sina): Information System for Submission of Thesis Title for Informatics Engineering Study Program Students (Case Study of the Faculty of Engineering, Ibnu Sina University) - David Saro; sherly agustini (YCMM, 2021)
Research is a term used in Indonesia to illustrate a scientific paper in the form of a written presentation of research results, discussing a problem in a particular field of science using applicable rules. The Informatics Engineering study program at Ibnu Sina University is still not effective and efficient in terms of campus services for final year students, especially when submitting the title of the final project because it is still using the manual method. The author uses the PHP programming language and MYSQL database which aims to build an information system for submitting the title of the final project which is expected to support and facilitate the process of submitting the title of the final project and easily get information about campus services, especially when submitting a final assignment at Ibnu Sina University.